Islamist Networks in Southeast Asia - Abdul Rahman Puteh, Al Chaidar; Kamil, Ade Ikhsan (Department of Anthropology, 2024)
Before we examine the Islamist networks in Southeast Asia, we need to clarify what we mean by Islamism and jihadism. These are two related but distinct concepts that often cause confusion and misunderstanding. Islamism is a political ideology that seeks to apply Islamic principles and values to public life. Jihadism is a militant strategy that uses violence and armed struggle to achieve Islamic goals. Islamism and jihadism are not synonymous, nor are they mutually exclusive. There are different types of Islamists and jihadists, and they do not always agree or cooperate with each other. We will also discuss some of the challenges and opportunities for dialogue and cooperation among Muslims and non-Muslims in the region, as well as the implications for regional and global security. The Islamist networks in Southeast Asia are diverse and complex, and they draw their inspiration and influence from various sources and categories of Islamist and jihadist ideologies.